Political Dynasties in General Elections According to Human Rights and A Comparison in Four ASEAN Countries - Saifulloh, Putra Perdana Ahmad; Barus, Sonia Ivana; Nggilu, Novendri M; Nur, Asrul Ibrahim; Sulaiman, Dindha Shahrazade (Faculty of Law Universitas Trunojoyo Madura, 2025)
The advantages of this article are discussing the Prohibition of Dynastic Politics from a Human Rights Perspective and Legal Formulas to Minimize Dynastic Politics as well as comparisons in three ASEAN countries. The research results concluded that the practice of dynastic politics cannot be separated from a human rights perspective, especially political rights for citizens. However, on the other hand, if it continues, the practice of dynastic politics can damage democratic principles. This is also based on comparisons in Singapore, Thailand and the Philippines. For this reason, in this article, the author provides a legal formula to minimize the negative excesses of dynastic politics, namely by strengthening the conditions for presidential/vice presidential candidates, gubernatorial candidates, mayoral candidates, and regent candidates in internal political parties. So that political parties will also strengthen the party system so as to avoid collusion and nepotism. To minimize dynastic politics, it is necessary to improve the culture within political parties. The reconstruction of the design of a democratic presidential candidacy is to prioritize the process of deliberation and consensus. Through the formation of the Party Consultative Assembly, it is hoped that it will be able to overcome and interpret the ideological ideals of political parties and the ideals of political leadership. This needs to be regulated in the Memorandum of Association/Articles of Association of Political Parties and the revision of the Political Party Law and Election Law. Furthermore, the analysis used normative legal research, including statutory, comparative, and conceptual methods.